2021
DOI: 10.1021/acs.langmuir.1c01144
|View full text |Cite
|
Sign up to set email alerts
|

Electric Charge-Induced Active Control of Nucleate and Rapid Film Boiling at the Nanoscale: a Molecular Perspective

Abstract: An effort has been made to understand the nucleate and the rapid film boiling phenomena under the influence of an electric field using a molecular viewpoint. The behavior of water molecules with a solid copper surface during the film boiling process in the presence of an electric field of different intensities has been studied. The molecular reasoning behind the suppression of the Leidenfrost phenomenon upon application of a uniform electric field along the heating substrate is established. Furthermore, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The three-phase contact line is the line separating three different phases for instance solid, liquid and gas. The line often appears in the physical processes like nucleate boiling, 30 meniscus characteristics, 30 crystallization occurrence 31 etc. The energy transport close to the three-phase contact line is important for understanding: the heat transfer under phase change, [32][33][34] the contact photothermally-induced bubbles grow, 35 different thermal capillary problems 36,37 or the various physical-based theranostic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The three-phase contact line is the line separating three different phases for instance solid, liquid and gas. The line often appears in the physical processes like nucleate boiling, 30 meniscus characteristics, 30 crystallization occurrence 31 etc. The energy transport close to the three-phase contact line is important for understanding: the heat transfer under phase change, [32][33][34] the contact photothermally-induced bubbles grow, 35 different thermal capillary problems 36,37 or the various physical-based theranostic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of phase transitions, molecular dynamics studies have shown that vapor condensation on the solid surface can be modulated by electric fields . The electric field strength and surface wetting properties have important effects on the boiling behavior of water molecule films . It can be found that in combination with the solid surface properties, the applied external electric field is expected to result in various interesting kinetic properties from fluids.…”
mentioning
confidence: 99%